2D phase contrast blood flow velocity measurements of the thoracic vasculature: comparison of the effect of gadofosveset trisodium and gadopentetate dimeglumine - Makowski, Marcus R.; Wiethoff, Andrea J.; Ebersberger, Hans U.; Botnar, Rene M.; Razavi, Reza; Schaeffter, Tobias; Greil, Gerald F. (International Journal of Cardiovascular Imaging, 2015)
The aim of this prospective study is to compare the performance of 2D time-resolved phase-contrast (PC) MRI prior to and after the administration of an intravascular (gadofosveset-trisodium) and extravascular (gadopentetate-dimeglumine) contrast agent in the same patient in the cardiovascular system. This study was approved by the ethics committee (Study-Number-07/Q0704/2) and registered with the MedicinesAndHealthcareProductsRegulatoryAgency (MHRA-Study-Number-28482/0002/001-0001, EudraCT-Number-2006-007042). All patients signed an informed consent. 20 patients were examined using a 1.5T MR-scanner and 32-channel-coil-technology. Gadopentetate-dimeglumine (GdD) and gadofosveset-trisodium (GdT) were administered in the same patient on consecutive days. Image quality, velocity-to-noise-ratios (VNRs) and standard-deviation of blood-flow-velocities (phase-noise) were compared between GdT, GdD and non-contrast-enhanced imaging. On both days pre- and post-contrast-scans were performed. The administration of GdT significantly improved the delineation of the perfused lumen and the VNR compared to GdD and non-contrast-enhanced imaging. Standard deviations of through-plane and in-plane velocity-measurements (phase-noise) were significantly reduced after GdT administration (p < 0.05). No significant differences (p > 0.05) were measured regarding absolute flow values prior to and after the administration of GdD and GdT. PC flow imaging benefits from the administration of an intravascular contrast agent by improving the delineation of the perfused lumen and reducing phase noise in flow measurements.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Aorta; Contrast media; Magnetic resonance imaging; Pulsatile flow